DEBUNKING TWO MYTHS ABOUT THE ORIGINS OF THE 2007-2010 FINANCIAL AND ECONOMIC CRISIS - Roderick Macdonald (Jurnal Ilmiah Ekonomi Bisnis, 2012)
The paper corrects two popular misconceptions about the originas of the 2007-2010 world financial and economic crisis. The first misconception was that it was caused by a greedy elite exploiting the ignorance and weakness of the poor. While there may have been irrepsoinible behavior within the finacial services, the story is rather one of a misguided benevolence of government bodies. The second misconception is that failed subprime mortgages were at the heart of misvalued mortgages backed securitites (and thus CDOs and CDOs squared) –the toxic assets that incarnated the finacial crash. Failed prime mortgages and jumbo mortgages were at least as important in thses toxoic assets.   Keywords : Financial crisis, sub-prime, mortgages, housing boom, government intervention